A comparison of the efficacy of single doses of albendazole, ivermectin, and diethylcarbamazine alone or in combinations against Ascaris and Trichuris spp. - Belizario V.Y; Amarillo M.E; Leon W.U. de; Reyes A.E. de los; Bugayong M.G; Macatangay B.J.C (The World Health Organization, 2003)
OBJECTIVE: To determine the efficacy of single doses of albendazole, ivermectin and diethylcarbamazine, and of the combinations albendazole + ivermectin and albendazole + diethylcarbamazine against common intestinal helminthiases caused by Ascaris and Trichuris spp. METHODS: In a randomized, placebo-controlled trial, infected children were randomly assigned to treatment with albendazole + placebo, ivermectin + placebo, diethylcarbamazine + placebo, albendazole + ivermectin, or albendazole + diethylcarbamazine. The Kato-Katz method was used for qualitative and quantitative parasitological diagnosis. The chi² test was used to determine the significance of cure rates, repeated measures analysis of variance for the comparison of mean log egg counts, the Newman-Keuls procedure for multiple comparison tests, and logistic regression for the comparison of infection rates at days 180 and 360 after treatment. FINDINGS: Albendazole, ivermectin and the drug combinations gave significantly higher cure and egg reduction rates for ascariasis than diethylcarbamazine. For trichuriasis, albendazole + ivermectin gave significantly higher cure and egg reduction rates than the other treatments: the infection rates were lower 180 and 360 days after treatment. CONCLUSION: Because of the superiority of albendazole + ivermectin against both lymphatic filariasis and trichuriasis, this combination appears to be a suitable tool for the integrated or combined control of both public health problems.